Aplikasi Mesin Cetak 3 Dimensi Untuk Pembuatan Saklar Tempat Duduk Pada Mobil KIA Carnival - Onery Andy Saputra; Sudiro Sudiro; Utomo Ramelan (Infotekmesin, 2020)
The types of automotive components today vary greatly. The presence of more components types make it difficult to find suitable automotive components. 3D Printing Machine is a new breakthrough to overcome these problems. This is based on the working concept of a 3-dimensional printing machine that make components done by the product design process and then print it through a 3-dimensional printing machine. This concept is further developed in the form of feasibility test of several aspects which are able to assess the results of the component products in order to be marketed. The purpose of this research is to see the feasibility of 3-dimensional printing machine products in terms of component shapes, component functions, terms of component dimensions and in the terms of similarity to the original product. The research methodology used in this research is descriptive quantitative comparative qualitative. The results of this study are, 1) The 3-dimensional product design has a similarity of 50%, but it is still lacking for the amount of fillet (upper angular curvature of the design). Meanwhile, for the size and shape in general have been made in accordance with the original product. 2) Forms that can be made from 3-dimensional printing still look less ergonomic. 4) The performance or function of the 3-dimensional printing component is able to match its function. 5) The weight of the 3-dimensional priting component is 47.19% heavier than the original component. 6) The dimensions of the components of 3-dimensional printing results on average for flat areas have a deviation of about 5.39% and for the profile field it reaches 35.29%.